Early Planning, Collaboration and the Role of Social Media: A Model for Future Event Success and Lessons Learned from Eclipse 2024 - Foster, Danielle C.; Savino, David M. (Journal of Knowledge Management Practice, 2024)
A total solar eclipse is a natural astrological phenomenon that is a special event in the infrequent interludes when it occurs. Two recent total solar eclipses in the United States occurred on August 21st, 2017, and April 8th, 2024. As was initially learned in 2017, such events are best experienced and handled if deliberate and detailed planning takes place before they occur. This paper examines the process that many cities, towns, brands, and companies across the country went through to prepare for and better handle the expected massive influx of interested observers and the important lessons learned that may have significant implications for local communities as well as business practices related to product development and promotion. The total solar eclipse on April 8th, 2024, showcased the potential for organizations and brands to create impactful campaigns that educate, engage, and drive brand awareness while promoting scientific inquiry and a sense of community.
Keywords: knowledge management; total solar eclipse; community planning; social media; product development and promotion; business knowledge lessons learned